2011
DOI: 10.1016/j.envres.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to allergenic pollens: A comparison between urban and rural areas

Abstract: a b s t r a c tBackground: Pollinosis is found more frequently in urban areas than in rural environments. This could be partly related to the different types of pollen exposure in these dissimilar areas. The objective of this study was to compare the distribution of pollen in these environments across an urbanization gradient. Methods: Daily pollen abundances were obtained in France using Hirst-type sensors. Sampling was conducted from January to June in 2003 and 2006 in a rural area, a semi-rural area and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 30 publications
(43 reference statements)
1
36
0
3
Order By: Relevance
“…Atmospheric pollen is the single most important inducer of allergies in susceptible individuals; thus, tight monitoring of phenological parameters is necessary to predict public risks. Plant pollination occurs on a seasonal basis, according to ecological and climatic factors that are specific for a region [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric pollen is the single most important inducer of allergies in susceptible individuals; thus, tight monitoring of phenological parameters is necessary to predict public risks. Plant pollination occurs on a seasonal basis, according to ecological and climatic factors that are specific for a region [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…are also abundantly present in this climatic region and might potentially play a role in allergic rhinitis while information is so far limited. Other allergenic plants frequently found in this region of France are grasses, ash, birch, oak, and mugwort [1,[10][11][12][13]. Several IgE-binding molecules of plantain pollen have been reported by immunoblots using patients' sera and mass spectrometry-based methods [8,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…English plantain typically flowers between April and September and shows an overlapping pollination season with grasses [2,5,6]. It grows mainly in temperate climate zones and is native in the north-east of France [5,[7][8][9][10]. Other Plantago spp.…”
Section: Introductionmentioning
confidence: 99%
“…The direct effect of air pollutants on pollen and on its allergenic potential is currently an important scientific subject. However, the effect of air pollutants on the allergenic potential of pollen is not yet completely clear, but it has been suggested that it contributes to increase allergic sensitisation (Traidl-Hoffmann et al, 2009;Bosch-Cano et al, 2011;Sousa et al, 2012).…”
mentioning
confidence: 99%